PENGARUH MODIFIKASI PERMAINAN TRADISIONAL TERHADAP HASIL BELAJAR PASSING SEPAKBOLA - Pramdhan, Kartono; Aulia, Rizki (Jurnal Olahraga, 2018)
The purpose of this study was to determine the effect of modification of traditional games on the learning outcomes of football extracurricular students at Madrasah Aliyah Negeri 1 Cimahi. This research is an experimental research using one group pretest posttest design method. The population of this research was all 15 extracurricular Madrasah Aliyah Negeri 1 Cimahi students. The sample determination in this study used a total sampling of 15 students. The instrument used in this study was a passing test with a time of 30 seconds by Majid Mohammed with a validity level of 0.63 and a reliability of 0.94. On the subject of research has increased the average ability of 2.53. This means that after being given the treatment of traditional game modifications an increase in learning outcomes passing football. Thus, it can be concluded that there is an influence of traditional game modification on the learning outcomes of passing students who take extracurricular football at Madrasah Aliyah Negeri 1 Cimahi.